Grammar rules ok!! : advanced. (Peer : Alquin)
A brand new, contrastive grammar textbook explaining all major grammar issues in an accessible, step-by-step approach, with an extensive and varied exercises book. Answers to the exercises, test papers plus keys available to teachers on the website.
Keywords: Engelse spraakkunst